Is corporate social responsibility a determinant of the capital structure of global systemically important banks? - Ndebele, Nomphumelelo Cindy (Department of Finance and Tax, 2021)
In the wake of the recent global financial crisis, the banking industry has come under heavy criticism for the negative externalities imposed on the economy and society. The distress of the financial system during the financial crisis has triggered public discussions about the role of bank capital structures in the stability of banking institutions. While it was previously thought that regulatory capital requirements are the sole determinant of bank capital structure, recent empirical studies suggest that, instead, the standard cross-sectional determinants that explain the capital structures of non-financial firms also apply to banks. The findings from these studies prompt further investigation into what other factors determine the capital structure of banks. More recently, engagement in Corporate Social Responsibility (CSR) activities has emerged as a vital dimension through which firms develop sustainable strategies that affect overall firm performance. In addition, the subsequent reporting of CSR performance has become increasingly important as more investors incorporate information about the social behaviour of firms in their investment decisions. This suggests that CSR has implications for the financing policies of firms. In light of the development of CSR as a relevant concept in the current corporate environment and especially in the banking industry, the goal of this study is to investigate whether CSR is a determinant of the capital structure of banks through a multiple regression analysis of panel data from 2009 to 2018 for a sample of 28 Global Systemically Important Banks. Using DataStream Refinitv ESG scores to proxy for CSR, the first hypothesis proposes that socially responsible banks tend to be less leveraged than those that are socially irresponsible due to the positive influence on equity financing from the lower costs of capital, informational asymmetries and risk associated with good CSR performance. The second hypothesis examines the effect of bank size on the proposed relationship. Initial results indicate no significant relation between aggregate CSR and bank leverage, however, further analysis shows a significant negative relationship between the governance dimension of CSR and bank capital structure, suggesting that the governance structures of banks are more relevant for bank capital structure decisions. Bank size is found to have no effect on the relationship. The findings from this study have important implications that are particularly relevant in today's financial environment as calls for the restoration of public trust in banking institutions accelerate.